Consulting patients in setting priorities in Myalgic Encephalomyelitis (M.E.) research: findings from a national on-line survey. Issue 1 (December 2015) - Childs, Nicola; Robinson, Lisa; Chowdhury, Sonya; Ogden, Clare; Newton, Julia
Plain english summary Myalgic encephalitis (M.E.) is a common condition, the cause of which is not known and there are no treatments available. In this study the national patient support group Action for M.E. sought the opinions of their members via an online survey as to what they felt should be future priorities for M.E. research. Respondents were asked what they considered first, second and third research priorities to be from a list of 13 pre-defined options. Individuals were invited to provide additional free text comments about Action for M.E.'s research priorities in general. Of the 1144 respondents: 822 had M.E.; 94 were a supporting a member of Action for M.E. ; 66 were carers for someone with M.E.; 26 were professionals with an interest in M.E.; 136 had a family member or colleague with M.E. Individuals selected more than one category as applicable. The top five research priorities identified were: disease processes to achieve a better understanding of the causes of M.E.; more effective treatments; faster and more accurate diagnosis; clinical course of M.E.; outcomes and natural history; and severely affected patients. Least popular priorities were: sleep; economic research towards identifying the cost of ME; and psychological aspects. Much of the free text comments emphasised the importance of funding biomedical research into disease processes to achieve a better understanding of the causes of M.E. Three themes were identified in relation to this topic: accurate diagnosis and awareness; risk factors and causes; drug development and curative therapies. In conclusion; individuals affected by M.E. have clear views regarding priorities for research investment. These have informed Action for M.E.'s ongoing research strategy and ultimately will inform national and international research priorities. Abstract Background The aim of this work was to involve patients in setting future priorities for myalgic encephalomyelitis (M.E.) research. Methods A national on-line survey was developed collecting structured and unstructured data. Respondents were asked what they considered Action for M.E.'s first, second and third research priorities to be from a list of 13 pre-defined options. Individuals were also invited to provide any additional free text comments about Action for M.E.'s research priorities in general. A total of 1144 individuals completed the on-line survey. Respondents were asked to indicate if: they had M.E. (n = 822; 90.4 %); were a supporting a member of Action for M.E. (n = 94; 10.3 %); carer for someone with M.E. (n = 66;7.3 %), professional with an interest in M.E. (n = 26;2.9 %); or had a family member or colleague with M.E. (n = 136;15 %). Individuals were able to select more than one category as applicable. Results The top five research priorities identified by the respondents were: disease processes to achieve a better understanding of the underlying pathology of M.E.; more effective treatments; faster and more accurate diagnosis; clinical course of M.E.; outcomes and prognosis; and severely affected patients. The lower research priorities identified were: sleep; economic research towards identifying the cost of ME for individuals and society; and psychological aspects. Much of the unstructured data provided by respondents emphasised the importance of funding biomedical research into disease processes to achieve a better understanding of the underlying pathology of M.E. Three themes were identified in relation to this topic: accurate diagnosis and awareness; risk factors and causes; drug development and curative therapies. Conclusions Individuals affected by M.E. have clear views regarding the most important priorities for research investment. These tended to focus on disease processes to achieve a better understanding of the underlying pathology of M.E. and have been used to inform Action for M.E.'s ongoing research strategy.